2020
DOI: 10.1175/jcli-d-19-0308.1
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of North Pacific Subtropical and Subarctic Oceanic Frontal Zones on the Wintertime Atmospheric Large-Scale Circulations

Abstract: An oceanic frontal zone is a confluent region of warm and cool ocean currents, characterized by a strong meridional gradient of sea surface temperature (SST). High-resolution SST observations show that the wintertime North Pacific exhibits a unique double-oceanic-front structure, with a subtropical frontal zone (STFZ) and a subarctic frontal zone (SAFZ), whose impacts on the weather and climate over the East Asia–North Pacific–North American region need further investigation. In this study, we conduct groups o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 53 publications
(65 reference statements)
3
18
0
Order By: Relevance
“…This result is similar to that of Huang et al [54], which showed that the climatic effects of the wintertime doubleoceanic-front structure in the NPac are characterized by weaker atmospheric responses to the northern ocean fronts. As noted previously [8][9][10][11][12]14,54], the turbulent heat fluxes may also play crucial roles in mesoscale air-sea interactions. Thus, we further analyzed the composite differences of spring turbulent heat fluxes between EddySSTA + N25N and SmthSST, and EddySSTA + S25N and SmthSST runs.…”
Section: Conclusion and Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This result is similar to that of Huang et al [54], which showed that the climatic effects of the wintertime doubleoceanic-front structure in the NPac are characterized by weaker atmospheric responses to the northern ocean fronts. As noted previously [8][9][10][11][12]14,54], the turbulent heat fluxes may also play crucial roles in mesoscale air-sea interactions. Thus, we further analyzed the composite differences of spring turbulent heat fluxes between EddySSTA + N25N and SmthSST, and EddySSTA + S25N and SmthSST runs.…”
Section: Conclusion and Discussionsupporting
confidence: 91%
“…We found that the LHF averaged over the KE ( 130 3b,d). Such overestimated surface turbulent heat fluxes (SHF and LHF) have also been reported in many previous wintertime model simulations [53,54]. Overall, the WRF model can roughly and reasonably reproduce the spatial patterns of SHF and LHF.…”
Section: Empirical Monte Carlo Significance Testsupporting
confidence: 80%
See 2 more Smart Citations
“…This result shows that during winter, the Pacific Subtropical oceanfront is stronger when the East Asian jet is intensified. The stronger oceanfront may feedback and help to maintain the downstream intensification of the upper-tropospheric jet through eddy activities and thermal wind balance, as suggested by a recent regional model study (Huang et al 2020). In addition, significant but weaker SST anomalies are also found in tropical Indian Ocean and equatorial central Pacific, in general similar to that with the variability of East Asian winter monsoon in Wang and Chen (2014), suggesting the connection between the variations of the two (Wang and Lu 2017;Chowdary et al 2019).…”
Section: Downstream Acceleration Eddy Activities and Pacific Subtromentioning
confidence: 81%